Global considerations in entrepreneurship education and training - Carvalho, Luisa Cagica 1970-; Daniel, Ana Dias (IGI Global, 2019)
"This book addresses the main issues of interest within the topics of entrepreneurship education and training. It focuses on entrepreneurial education at higher and lower levels of education, as well as its importance for local communities and companies, considering a broad geographic overview"--